Flow injection determination of catechol based on polypyrrole-carbon nanotube-tyrosinase biocomposite detector - Ozoner, Seyda Korkut; Yalvac, Mevra; Erhan, Elif (ELSEVIER, 2010)
A flow injection catechol biosensor based on tyrosinase entrapped in carbon nanotube modified polypyrrole biocomposite film on a glassy carbon surface has been developed. Amperometric response was measured as a function of concentration of catechol, at a fixed bias voltage of -50 mV at a flow rate of 1 mL/min. The proposed biosensor exhibited impressive analytical performance such as a linear range between 3 and 50 mu M, a short response time (10 s), a detection limit of 0.671 mu M and an excellent operational (with a relative standard deviation of 0.54%) and long-term stability (85% remained after 10th week). A comparison of the analytical parameters of the developed biosensor with polypyrrole/tyrosinase film electrode was performed in the study. CNT was shown to enhance the electron transfer between the electrode and enzyme and capable to carry higher bioactivity owing to its intensified surface area. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Flow injection; Biosensor; Polypyrrole; Carbon nanotube; Catechol; Tyrosinase; COMPOSITE ELECTROCHEMICAL BIOSENSORS; AMPEROMETRIC BIOSENSOR; PHENOLIC-COMPOUNDS; IMMOBILIZATION; FILM; CONSTRUCTION; LACCASE; Materials Science; Physics